Vesicular (liposomal and nanoparticulated) delivery of curcumin: a comparative study on carbon tetrachloride–mediated oxidative hepatocellular damage in rat model - Choudhury ST (Dove Medical Press, 2016)
Somsubhra Thakur Choudhury,1 Nirmalendu Das,2 Swarupa Ghosh,2 Debasree Ghosh,2 Somsuta Chakraborty,2 Nahid Ali1 1Infectious Diseases and Immunology, 2Drug Development, Diagnostics and Biotechnology, CSIR-Indian Institute of Chemical Biology, Kolkata, West Bengal, India Abstract: The liver plays a vital role in biotransforming and extricating xenobiotics and is thus prone to their toxicities. Short-term administration of carbon tetrachloride (CCl4) causes hepatic inflammation by enhancing cellular reactive oxygen species (ROS) level, promoting mitochondrial dysfunction, and inducing cellular apoptosis. Curcumin is well accepted for its antioxidative and anti-inflammatory properties and can be considered as an effective therapeutic agent against hepatotoxicity. However, its therapeutic efficacy is compromised due to its insolubility in water. Vesicular delivery of curcumin can address this limitation and thereby enhance its effectiveness. In this study, it was observed that both liposomal and nanoparticulated formulations of curcumin could increase its efficacy significantly against hepatotoxicity by preventing cellular oxidative stress. However, the best protection could be obtained through the polymeric nanoparticle-mediated delivery of curcumin. Mitochondria have a pivotal role in ROS homeostasis and cell survivability. Along with the maintenance of cellular ROS levels, nanoparticulated curcumin also significantly (P<0.0001) increased cellular antioxidant enzymes, averted excessive mitochondrial destruction, and prevented total liver damage in CCl4-treated rats. The therapy not only prevented cells from oxidative damage but also arrested the intrinsic apoptotic pathway. In addition, it also decreased the fatty changes in hepatocytes, centrizonal necrosis, and portal inflammation evident from the histopathological analysis. To conclude, curcumin-loaded polymeric nanoparticles are more effective in comparison to liposomal curcumin in preventing CCl4-induced oxidative stress–mediated hepatocellular damage and thereby can be considered as an effective therapeutic strategy. Keywords: reactive oxygen species, mitochondria, apoptosis, antioxidants, histopathology, Western blot